Perlindungan Konsumen dalam Rekayasa Rating Penilaian pada Aplikasi Shopee Perspektif Mazhab Imam Asy-Syafi’i: Studi Kasus Pengguna Aplikasi Shopee di Desa Tembung Kecamatan Percut Sei Tuan - Muhammad Iqbal; Rahmat Hidayat (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
High competition encourages business actors to use various methods to market their products, without paying attention to applicable rules and laws. One of the strategies used is Rating Engineering. Rating engineering is a false assessment that is often used to increase the reputation of a shop so that it is more trustworthy when people visit it when they want to shop with the aim of making buyers interested and concluding that the shop is a shop that is very popular on its site. The existence of rating engineering activities makes consumers worried about the authenticity of the goods being sold. This research discusses legal protection and the perspective of the Imam Syafi'i School regarding rating engineering activities. The aim of this research is to determine the impact of rating engineering using fake orders and consumer protection against the practice of rating engineering. The results obtained are that consumer protection has been very well regulated from a religious perspective, namely the Al-Qur'an and Hadith as well as from a legal perspective in Indonesia in Law No. 8 of 1999, so this is very strong to follow in terms of consumer protection and also obligations. business actors in carrying out their business can create a society that behaves correctly and honestly in every implementation. According to the perspective of the Imam Asy-Shafi'i School, the practice of rating engineering carried out by several online business actors on the Shopee application is haram because it violates buying and selling ethics and business ethics by committing fraudulent acts in their promotions in the marketplace.